A fixed point index approach to a third order nonlocal boundary value problem - Zima, Mirosława; Szajnowska, Gabriela (Topological Methods in Nonlinear Analysis, 2025)
Using a topological approach we study the existence of positive solutions to a third order differential equation subject to nonlocal boundary conditions. Our method is based on the fixed point index theory in cones. The main results extend and complement some previous works and are illustrated by suitable examples.